Twin Birth Order, Birthweight and Birthweight Discordance: Any Relationship? - Onyiriuka, Alphonsus N (Nepal Journal of Obstetrics and Gynaecology, 2011)
Aim: To assess the truthfulness of this common concept that first-born twins are usually heavier than their second-born siblings at birth. Methods: In a series of 104 sets of live-born twins, the birth weights of first-born twins were compared with those of their second-born siblings, after controlling for gender. Their intra-pair birthweight differences were determined and twin pairs whose birthweight difference was 15% or more were designated as discordant. Results: Twin I was heavier than Twin II in 61.5% of cases while Twin II was heavier than Twin I in 28.9% of cases. Twins I and II had equal birth weight in 9.6% of cases. Comparing the mean birthweight of the first-born-male twin with that of second-born- male twin, it was 2515 + 427g [95 % Confidence Interval, CI = 2402 - 2628) versus 2432 + 435g (95% C I = 2321 - 2543) p>0.05. The mean birthweight of first-born-female twin was 2326 + 445g (95% CI =2214 - 2439) while that of the second-born-female twin was 2325 + 501g (95% CI = 2197 - 2453) p>0.05. When the birthweight difference exceeded 750g, the probability that Twin I will be heavier than Twin II was 83.3% (5 of 6). Conclusion: Although the first-born twin was more often heavier than their second-born siblings, either could weigh more or less at birth. The larger the birthweight difference between growth-discordant twin pair, the greater the probability that the heavier twin would be delivered first. Keywords: Birth order relative birth weights, birthweight discordance, twins DOI: http://dx.doi.org/10.3126/njog.v6i1.5252 NJOG 2011; 6(1): 46-50